Efeitos do tratamento intraperitoneal com lidocaína ou bupivacaína na sobrevida de ratos submetidos a peritonite - Marcos Celio Brocco (2009)
Purpose: To study the effects of peritoneal lavage with a 2% lidocaíne or 0,5% bupivacaíne solution, on the survival of the rats submitted to peritonitis caused by their own feces. Methods: Sixty Wistar rats, weighting between 300 g and 330 g (mean, 311,45 ±9,67 g), were submitted to laparotomy 6 hours following induction of fecal peritonitis. Animals were randomly divided into five groups of 12 each as follows: 1- Control no therapy; 2- Drying of the abdominal cavity; 3- Peritoneal lavagewith 3 mL saline solution 0,9% and drying; 4- Peritoneal lavage with 30 mg/kg (0,5 mL) 2% lidocaíne diluited with 2,5 mL saline solution 0,9% and drying; 5- Peritoneal lavage with 8 mg/kg (0,5 mL) 0,5% bupivacaíne diluited with 2,5 mL saline solution 0,9% and drying. Animals that died were submitted to necropsy and the time of their death recorded; survivors were killed on the post-operation 11th day and necropsied.Results: Death occurred within 52h in all animals of group 1; within 126h in 100% of those of group 2; within 50h in 50% of those of group 3. All animals of groups 4 and 5 survived. Survival on the 11th day was higher in groups 3,4 and 5 than in groups 1 and 2 (p<0,001), and higher in groups 4 and 5 than in group 3 (p<0,01). Conclusion: Peritoneal lavage with 30 mg/kg lidocaíne or 8 mg/kg bupivacaíne, prevented the mortality of all animals with fecal peritonitis.